EVALUASI PENGGUNAAN BUBUK BIJI ALPUKAT (Persea americana MIL) DALAM PAKAN TERHADAP PERFORMA PRODUKSI PUYUH - Puspita Cahya Achmadi; Korbinianus Feribertus Rinca; maria tarsisia luju; Roselin Gultom; Yohana M.F Bollyn (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2023)
A by-product of plantation waste of avocado seed (Persea americana Mill) contains nutrients including crude fat, crude fiber, crude protein, ash, Ca, P, Energy Metabolism, and polyphenol complex. This research aims to evaluate the effect of using avocado seed meal in feed on quail performance including feed consumption, hen day production, feed conversion, and income over feed costs. This research was conducted in two stages, the first stage was laboratory research. The second phase of the experimental research requires 120 quails aged 14 days. This study used RAL with 4 treatments and 6 replications. Treatment was given P0 (100% complete), P1 (98,5% complete feed + 1.5% avocado seed meal), P2 (98% complete feed + 2.0% avocado seed meal), P3 (97,5% complete feed + 2.5% avocado seed meal). The results of this study indicate that evaluating the application of avocado seed meal to a level of 2.5% cannot increase feed consumption, and HDP and IOFC cannot reduce feed conversion of quail.